2004
DOI: 10.1111/j.1755-6988.2004.tb00094.x
|View full text |Cite
|
Sign up to set email alerts
|

Teen Court: What Jurors Can Tell Us About the Process

Abstract: Teen courts are on the increase throughout the United States. These courts provide an opportunity for youth offenders to receive sentences from their adolescent peers rather than from an adult panel or judge. Yet, we know t very little about the teen jurors' perspective or whether their sentences reflect restorative justice principles. In more than 100 youth juror surveys, t teens describe their experiences as they develop sentences consistent with restorative justice tenets. Through their participation, youth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 15 publications
0
11
1
Order By: Relevance
“…The failure of the Urban Institute study to control for differences between the control and treatment groups, for instance, suggests the possibility that differences in outcomes could have been the result of pre-program differences rather than TC participation. These flaws are not unique and are found in other TC studies (e.g., Seyfrit et al 1987;Rasmussen and Diener 2005;Forgays et al 2004). Even those studies that claim to be rigorous failed to collect recidivism data on control groups, thus limiting their usefulness in evaluating program efficacy (e.g., LoGalbo and Callahan 2001;Weisz et al 2002).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The failure of the Urban Institute study to control for differences between the control and treatment groups, for instance, suggests the possibility that differences in outcomes could have been the result of pre-program differences rather than TC participation. These flaws are not unique and are found in other TC studies (e.g., Seyfrit et al 1987;Rasmussen and Diener 2005;Forgays et al 2004). Even those studies that claim to be rigorous failed to collect recidivism data on control groups, thus limiting their usefulness in evaluating program efficacy (e.g., LoGalbo and Callahan 2001;Weisz et al 2002).…”
Section: Discussionmentioning
confidence: 93%
“…Many TC studies have not used comparison groups, thus limiting their ability to assess the program's effectiveness (e.g., Forgays et al 2004;Garrison 2001;Harrison et al 2000;Minor et al 1999). Minor et al (1999) examined TC respondents over three different time periods and found a recidivism rate of 31.1%.…”
Section: Teen Courts: Description and Previous Researchmentioning
confidence: 98%
“…Social control and social learning theories argue that offending youths are more responsive to their peers than to adults. In a study by Forgays et al. (2004), volunteers stated that offenders value their dispositions because they care about their peers' opinions, and the youth court process is fairer than juvenile court because the jury is comprised of their peers.…”
Section: Conceptual Framework and Results: Focus Group Datamentioning
confidence: 99%
“…In some courts, youths also serve as judge, attorneys, bailiff, and clerk. The goals of youth court are to reduce the backlog of cases in the juvenile justice system, reduce court costs, lower recidivism rates, and provide opportunities for offenders and volunteers to learn law‐related citizenship and personal skills (Lyles & Knepper, 1997, cited in Forgays, DeMilio, & Schuster, 2004; Maloney & Holcomb, 2001, cited in Forgays et al., 2004; Pearson & Jurich, 2005; Schneider, 2008). Dispositions are based on the restorative justice model, and are designed to educate offenders, discourage future crime, and encourage pro‐social behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation